Cytosolic proline is required for basal freezing tolerance in Arabidopsis. (10th October 2021) - Hoermiller, Imke I.; Funck, Dietmar; Schönewolf, Lilli; May, Henrik; Heyer, Arnd G.
Abstract: The amino acid proline accumulates in many plant species under abiotic stress conditions, and various protective functions have been proposed. During cold stress, however, proline content in Arabidopsis thaliana does not correlate with freezing tolerance. Freezing sensitivity of a starchless plastidic phosphoglucomutase mutant ( pgm ) indicated that localization of proline in the cytosol might stabilize the plasma membrane during freeze–thaw events. Here, we show that re‐allocation of proline from cytosol to vacuole was similar in the pyrroline‐5‐carboxylate synthase 2–1 ( p5cs2–1 ) mutant and the pgm mutant and caused similar reduction of basal freezing tolerance. In contrast, the starch excess 1–1 mutant ( sex1‐1 ) had even lower freezing tolerance than pgm but did not affect sub‐cellular localization of proline. Freezing sensitivity of sex1‐1 mutants affected primarily the photosynthetic electron transport and was enhanced in a sex1‐1::p5cs2–1 double mutant. These findings indicate that several independent factors determine basal freezing tolerance. In a pgm::p5cs2–1 double mutant, freezing sensitivity and proline allocation to the vacuole were the same as in the parental lines, indicating that the lack of cytosolic proline was the common cause of reduced basal freezing tolerance in both mutants. We conclude that cytosolic proline is an important factor in freezing tolerance of non‐acclimated plants. Abstract : Arabidopsis thaliana mutants defective in either starch or Pro synthesis reveal the importance of Pro abundance in the cytosol for freezing tolerance of plants before cold acclimation. However, freezing sensitivity of sex1‐1 mutants, which are defective in starch phosphorylation, is instead caused by damage to chloroplasts.